Pattern and Evolution of C4d Staining of Ischemic Myocardial Injury: Implications for the Interpretation of Post-Transplant Endomyocardial Biopsies - Hudacko, MD, Rachel; Varghese, MD, Sumi; Fyfe, MD, Billie (North American Journal of Medicine and Science, 2012)
C4d immunohistochemical staining is a marker of recent classical pathway complement activation that is useful for evaluation of antibody-mediated rejection in transplant biopsies. C4d also stains areas of myocyte necrosis. We describe the pattern and intensity of myocyte, interstitial, and microvascular staining at different stages of ischemic injury/infarction in the non- transplant setting. Thirty autopsies with ischemic injury were reviewed. Nine acute myocardial infarction, 3 contraction band necrosis, 9 subendocardial ischemic, and 9 chronic ischemic injury/scarring cases were stained with polyclonal antibody for C4d. Results: Acute myocardial infarction and subendocardial ischemic injury cases showed strong staining of necrotic myocytes; larger infarcts showed more intense peripheral versus central staining. Subendocardial ischemic injury was easier to quantify versus H&E staining. Necrosis with contraction bands was highlighted in individual myocytes. Two of 9 cases of chronic ischemic injury/scarring showed only rare positive cells. C4d was noted to highlight amyloid in 4 cases. Microvascular staining was noted in only 2 cases, was faint and not associated with injured areas. Autolysis had no effect on staining. C4d is a useful diagnostic tool to highlight necrotic myocytes, especially in the absence of large areas of obvious necrosis. It can be used to differentiate true from artifactual contraction band injury and can be used on autolyzed material. Microvascular staining is not seen around areas of infarction. This finding may help in the interpretation of perioperative ischemic injury versus humoral rejection in heart transplants, wherein microvascular staining in post-implantation biopsies should prompt additional clinical investigations to rule out humoral rejection.